Excavating Values and Character through Angkola-Mandailing Proverbs - arianto, Arianto (ELT (English Language Teaching Prima Journal), 2020)
ABSTRACT It has been undeniable that language variety makes Indonesia world-widely recognized as a unity in diversity country. Language itself is projected to build harmony among other through social interaction. In Indonesia, such interactions are commonly beautified with the existences of culturalbased proverbs. As an ethnic group, Angkola-Mandailing (AM) society has been known with its uniqueness in conducting the proverbs in any traditional event, both joyful celebration (siriaon) and condolences one (siluluton). Even, in any casual interaction among the citizen. AM proverbs are highly considered as philosophical and culturally valuable. This research is pointed to describe the functions of proverbs and excavating values and character within AM proverbs. Descriptivequalitative was conducted to analyze the data. Further, ethnographic content analysis was also employed to interpret the substances of data analysis. The findings show that AM proverbs are functioned to address advice, to admonish, and to satirize. Moreover, the findings also display that brotherhood, togetherness, patience, hard-work, sincerity, and respect other people are values and characters could be drawn within. To be concluded, the findings are worthwhile to be internalized at present. Keywords: Angkola-Mandailing, proverbs, social functions, interpretations